Penerapan Teori Graf pada Topologi Matriks Jaringan Distribusi Radial dalam Menentukan Losses - Adnan, Muhammad; Abidin, Zainan (Politeknik Negeri Ujung Pandang, 2016)
Losses in distribution network of electrical power system with radial system topology can be calculated using Graf Theory. Graf Theory uses nodes and branches that are exist in radial network and convert them in matrices equations. This method is used to determine injection current in losses calculation in every single network branch.